ANALISIS KELAYAKAN FINANSIAL WIRAUSAHA PRODUKTIF SAMCURRY (SAMOSA CURRY) MAHASISWA - Alexander, Yohanes; Mushollaeni, Wahyu; Esika, Yulita; Emon, Friska Astuti; Kandar, Augrasia Stefani Dirga; Giur, Gudelia Trivoni (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
The analysis of the financial feasibility of the production of a food product is carried out through the calculation of the financial feasibility analysis of the business. The analysis involves the calculation of investment costs, production costs, Cost of Goods Sold (COGS), Break Event Point (BEP), and RC/Ratio. In this study, a financial feasibility analysis was carried out to determine the financial performance of the production of SAMCURRY samosa snacks produced by a group of entrepreneurial students at Tribhuwana Tunggadewi University. The purpose of the study is to obtain the results of the analysis of financial feasibility and profit and loss projections from the SAMCURRY samosa product business typical of Malang. The method used is qualitative descriptive with business cash flow data and business development projections. The calculation results gave an HPP result of Rp. 5337,- with a mark up taken by the company of 87%, so that the selling price for 1 pack of SAMCURRY with 3 cooked samosas was Rp. 10,000,-. The BEP Unit value is 568 units (samosa/year) and the BEP Price is Rp. 5,680,920/year. RC/Ratio gives a result of 1.87, so it can be stated that SAMCURRY’s production business is feasible or efficient and the business is profitable. The annual profit plan is Rp. 92,329,671/year. In addition to the production of mature SAMCURRY, samosa is also marketed in the form of frozen processing in vacuum packaging. The HPP value is Rp. 9309,- with a mark up taken by the company of 93%, so the selling price for 1 pack containing 6 samosas in vacuum packaging is Rp. 18,000,-. The production of this freeze-vacuum samosa is worth continuing the business, because it can provide business profits and the RC/Ratio value is 1.93. The BEP value of the unit is 667 (samosa/year) and the BEP Price is Rp.12,000,017 per year